2019
DOI: 10.1021/acsnano.9b06578
|View full text |Cite
|
Sign up to set email alerts
|

“Seeing” and Controlling Photoisomerization by (Z)-/(E)-Isomers with Aggregation-Induced Emission Characteristics

Abstract: Efficient photoisomerization of chromophores is important in living systems, and structural constraints of protein pocket on chromophores are the probable reason for moving their dynamic reaction equilibrium forward. On the other hand, photochemical reaction to switch a molecule from one isomer to the other with different geometry and property in a high yield will continue to play a vital role in the synthetic chemistry and material science. Because of the important role of efficient photoisomerization, a biom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 38 publications
1
31
0
Order By: Relevance
“…[95][96][97][98][99][100] Notably, many exclusive structures and properties have only been discovered in the aggregate state but not in molecular species. [101][102][103][104] In the following sections, we build a relationship between structures and properties at the aggregate level. The structures are summarized from two perspectives, describing "static" aggregates and "dynamic" aggregates.…”
Section: Introductionmentioning
confidence: 99%
“…[95][96][97][98][99][100] Notably, many exclusive structures and properties have only been discovered in the aggregate state but not in molecular species. [101][102][103][104] In the following sections, we build a relationship between structures and properties at the aggregate level. The structures are summarized from two perspectives, describing "static" aggregates and "dynamic" aggregates.…”
Section: Introductionmentioning
confidence: 99%
“…[13] Copyright 2017, American Chemical Society; Reproduced with permission. [14] Copyright 2019, American Chemical Society synthetic procedures, a convenient method for the fabrication of smart fluorescent materials is provided in this work by simply attaching AIEgens into polymer backbones through hydrogen bonding-driven supramolecular assembly. Apart from acting as the binding forces basically, the application of hydrogen bonding can also take part in adjusting fluorescent properties of the inherent AIEgens.…”
Section: Aie Systems Involving Hydrogen Bonding-driven Supramolecularmentioning
confidence: 99%
“…Interestingly, these UPy‐modified TPE molecules can also undergo photoisomerization as controlled by the different polymerizability of the monomers and visualized by the altered fluorescence of the system (Figure 2B). [ 14 ] By comparing the isomerization yields in different solvent conditions, higher assembly degree obviously contributed largely to the inhibition of backward reaction and promoted the isomerization efficiency, further causing the sphere‐to‐fiber transformation and the fluorescence change from weak green to bright blue, providing real‐time monitoring of the photoisomerization processes.…”
Section: Aie Systems Involving Hydrogen Bonding–driven Supramolecularmentioning
confidence: 99%
“…[102] Tang et al reported an approach for "seeing" and controlling the photo-isomerization of the AIE-active 2-ureido-4[1H]-pyrimidinone functionalized TPE isomers. [103] Lu et al constructed a novel photoswitch by making use of the photo-isomerization between an AIE-active liquid crystal molecule ((Z)-CN-APHP) and its E isomer ((E)-CN-APHP) upon alternating light irradiation at 440 and 254 nm. [104] The investigation of photo-isomerization based on AIEgens contributes to a deeper exploration of the AIE mechanism.…”
Section: Photo-isomerizationmentioning
confidence: 99%